Potensi Arang Aktif yang Terbuat dari Kulit Biji Nyamplung Sebagai Adsorben Logam Berat Kromium (VI) - Nadhifah Al Indis (Universitas Duta Bangsa Surakarta, 2021)
The important issues in era industrial 4.0 is the problem of environment polluted by heavy metal waste water, especially chromium (VI). Chromium (VI) can accumulate in aquatic organisms and enter the human body, which caused the skin rashes, cancer, and genetic mutations. One way to reducing chromium (VI) in waste water using adsorption method with activated carbon made from Nyamplung (Calophyllum inophyllum) seed shell. Biomass was carbonized to produce carbon (yield 22.36%), and then it activated by H2SO4 (50:50) solution. Based on observations, activated carbon has a black color and contains carbon-carbon cross-links (FTIR test). Gravimetric method to analyze of water content obtained 5.21%. Analysis of porous material using the BET and BJH methods, obtained the surface area was ​​61,339 m²/g, the pore diameter was 3.781 nm, and the pore volume was 0.015 cm3/g. Adsorption test of 0.1g activated charcoal against 50mL of chromium (VI) with various concentrations 25, 50, 75, and 100 mg/L, at pH = 1, timing 150 minutes, and 500 rpm batch rotation speed, obtained the adsorption capacity of activated carbon (qt) is 8.57 mg/g.